Dari Toleransi ke Koeksistensi: Eksplorasi Konseptual Pendidikan Islam dan Multikulturalisme dalam Menghadapi Radikalisme - Ardhy, Andi Anugrah Surya (Educatia : Jurnal Pendidikan dan Agama Islam, 2024)
This research aims to conceptually explore the integration of multicultural values ​​in Islamic education and its potential to overcome radicalism and promote a more inclusive and peaceful society. The researcher used a library research approach. This research examined various scientific books, journals, research results, and academic discussions relevant to Islamic education and multiculturalism. Hermeneutic analysis techniques deepen understanding of how Islamic education can be enriched with a multicultural approach. Findings show that the current Islamic education curriculum often lacks comprehensive integration of multicultural aspects that can encourage active coexistence. Therefore, this research proposes curriculum reform that educates about tolerance and actively promotes coexistence through a more inclusive and transformative approach. It includes developing teaching materials to encourage a deep understanding of other religions and active social engagement among students from diverse cultural and religious backgrounds. Islamic education integrated with multicultural values ​​has significant potential to reduce radicalism and strengthen the foundations of a tolerant and harmonious society. Implementation requires collaboration between policymakers, educators, and community stakeholders to develop and implement curricula supporting coexistence and diversity. This research provides new insights into the strategic role of Islamic education in the current global context and offers practical recommendations for educational reform oriented towards coexistence and inclusivity.